Addressing smoking among people living with HIV: a cross-sectional survey of Australian HIV health practitioners' practices and attitudes. Issue 4 (3rd April 2019) - Bell, Stephanie K.; Mena, Gabriela; Dean, Judith; Watts, Peter; Howard, Chris; Boyd, Mark; Gilks, Charles; Gartner, Coral
ABSTRACT: People living with HIV (PLHIV) have high rates of tobacco smoking, and smoking is a leading cause of premature mortality and morbidity. It is important to understand HIV healthcare providers' practices and attitudes towards addressing smoking with their patients. An online survey that measured: (i) use of the 5A framework for addressing smoking (Ask, Assess, Advise, Assist, Arrange) and (ii) attitudes and barriers to addressing smoking cessation was distributed by relevant professional bodies. Eligible participants were Australian health practitioners providing healthcare to PLHIV. Of the 179 respondents, most reported practising at least one of the 5As: Ask (94%); Assess (78%); Advise (82%); Assist (89%); and Arrange (73%). Practising the full 5A framework (completing at least one activity from each A) was less common (62%) and associated with having undertaken smoking cessation training (OR 2.1, CI 1.1–3.9), being a medical practitioner (OR 6.0, CI 3.1–11.6), having greater perceived knowledge and resources (OR 1.7, CI 1.3–2.4) and more positive attitudes (OR 1.5, CI 1.1–2.0). Common barriers to delivering cessation assistance related to knowledge and availability of resources. Development and greater dissemination of effective smoking cessation training and resources may be required to ensure healthcare practitioners have the capacity to complete all aspects of the 5A framework for smoking cessation and support their patients with HIV who smoke.